Farmers’ adaptation strategies to climate change on agricultural production in Arsi zone, Oromia National Regional State of Ethiopia - Dawid, Ibsa; Boka, Ephrem (Frontiers in Climate, 2025)
Climate change has a greater influence on agricultural production due to the effects of floods, droughts, and crop pests. The objective of the study was to explore farmers’ perceptions of climate change, adaptation strategies, constraints to adaptation strategies, and identify factors affecting the choice of climate change that affect adaptation strategies for agricultural production. Data was collected from 303 households selected using a multistage sampling technique to collect data using structured questionnaires. Descriptive statistics, Mann–Kendall statistical test, the weighted average index, and a multivariate probit model were used. The result shows that farmers used multiple adaptation strategies, mostly improved varieties, improved livestock, and mixed farming. Farmers’ choices of adaptation strategies were affected by education, household size, cooperative membership, extension services, climate information, perception of climate change, and farm income. Thus, efforts to create awareness about climate change through mass media, extension services, and enabling cooperative unions are essential.